Antioxidant Capacity and Radical Scavenging Activity of Silybum marianum and Ceratonia siliqua - Akkaya, Hatice; Yilmaz, Okkes (Foundation Environmental Protection & Research-Fepr, 2012)
The aim of this study is to investigate the protective effects of Silybum marianum and Ceratonia siliqua extracts on unsaturated fatty acids and the suppressive effects on the Fenton reagent in lipid peroxidation (LPO). The LPO levels in the Silybum marianum and Ceratonia siliqua groups were higher than the control group (p<0.001), whereas; these levels were lower by about 50% than that of the Fenton R group (p<0.001). In addition, it was determined that S. marianum and C. siliqua extracts had scavenging effect on the DPPH radical as it is in quercetin (p>0.05). The fatty acid levels in the Fenton R group were lower than that of the control group (p<0.001). However, fatty acid levels in the S. marianum and C. siliqua groups were higher than the Fenton R group (p<0.001). The Linoleic acid level in the S. marianum group was slightly lower than the control group (p<0.01) but the oleic acid level was higher than the control group (p<0.001). Our results confirm that extracts of S. marianum and C. siliqua decreased the LPO level and protected markedly the unsaturated fatty acids against free radicals.
Silybum marianum and Ceratonia siliqua'nın Antioksidan Kapasitesi ve radikal koruyucu Aktivitesi
Keywords: Ceratonia siliqua; Fenton reagent; lipid peroxidation; radical scavenging effects; Silybum marianum